Analisis Pembentukan Karakter Bernalar Kritis melalui Metode Bercerita pada Peserta Didik Kelas IV SD Negeri Magelaran - Andriana, Encep; Rokmanah, Siti; Lingga, Alviani (Lentera: Jurnal Ilmiah Kependidikan, 2023)
Critical reasoning is one of the profiles of Pancasila learners that must be learned by students, namely building links between various information, analyzing information, evaluating and concluding. Critical reasoning character can be formed through storytelling method. The purpose of this study was to analyze the formation of critical reasoning character, through the storytelling method to students. This research uses a qualitative method descriptive approach, with the aim of describing the events that took place during data collection. Data collection techniques in this study used observation, interviews, and questionnaires, with the subject of grade IV students of SDN Magelaran totaling 32 students. The results showed that the formation of critical reasoning character through the storytelling method in students was quite good. Activities that are fun and attract the attention of students affect the formation of critical reasoning character. Efforts that can be made are to give direction on attitudes that are deemed less in accordance with the meaning of critical reasoning.